Impact of a Comprehensive Clinical Pharmacist Intervention on Medication Safety in Patients on High-Risk Prescription Drugs Following Hospitalization - Loay Ali Hassan Al Bayat; Mohammed Abdullah Abuqreen; Feras Ahmed Habib Aldhamen; Fadhel Abdulla Salman Alnaser; Hani Ali Abdullah Al-Basri; Abdullah Hussain Ahmed Alnahwi; Abdulwadood Abdullah Almahroos; Mahmoud Ali Alhabib; Abbas Ahmed Alradwan; Basim Abdullah Alsobikhi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Adverse drug events (ADEs) significantly impact patients post-hospitalization, particularly older adults prescribed high-risk medications such as anticoagulants, diabetes treatments, and opioids. This study evaluated the impact of a multifaceted clinical pharmacist-led intervention on medication safety after hospital discharge Methods: Patients aged 50 and older, recently discharged and prescribed at least one high-risk medication, were randomized into two groups: an intervention group receiving a pharmacist-led program (home visit, education, EHR documentation, and follow-up calls) or a control group receiving mailed educational materials. Outcomes included ADEs and clinically significant medication errors assessed over 45 days Results: Among 361 participants, 27.7% experienced at least one ADE, and 18% had a clinically significant medication error. The intervention group showed no significant reduction in ADEs (IRR 0.97, 95% CI 0.70–1.34) or errors (IRR 0.81, 95% CI 0.53–1.23) compared to controls. Emergency visits and rehospitalizations were similar across groups Conclusion: The intervention did not significantly reduce ADEs or medication errors. Further refinement and evaluation of post-discharge medication safety interventions are essential to address this high-risk period